8 The Statutes at Large of South Carolina: Containing the Acts Relating to Corporations and the Militia 485 (David J. McCord ed., 1841) - (:unkn) unknown (My University, 1794)
Organized its militia "in conformity with the act of Congress." The South Carolina militia was "every citizen who shall, from time to time, arrive at the age of eighteen years." It excluded "all persons under the age of eighteen, and above the age of forty-five years." Additionally, "all free white aliens or transient persons, above the age of eighteen and under the age of forty-five years, who have resided or hereafter shall or may reside in this state for the term of six months [were] subject and liable to do and perform all patrol and militia duty which shall or may be required by the commanding officer" of the district." The required arms were the same as the federal Uniform Militia Act.
Keywords: MILITIAS